2020
DOI: 10.1101/2020.03.10.985879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ventral tegmental dopamine neurons control the impulse vector during motivated behavior

Abstract: The Ventral Tegmental Area (VTA) is a major source of dopamine, especially to the limbic brain regions. Despite decades of research, the function of VTA dopamine neurons remains controversial. Here, using a novel head-fixed behavioral system with five orthogonal force sensors, we show for the first time that distinct populations of VTA dopamine activity 5 precisely represent the impulse vector (force exerted over time) generated by the animal.Optogenetic excitation of VTA dopamine neurons quantitatively determ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 42 publications
(11 reference statements)
3
29
0
Order By: Relevance
“…Our design is directly inspired by the hierarchical organization of the motor system in vertebrates (16), and by its ability to pursue a hierarchy of goals in parallel, despite a complex and unpredictable environment (52). This basic design is in agreement with extensive experimental work in neuroscience (5, 6, 7, 8, 20, 21, 26, 27), and the efficacy of this design supports input control hierarchies as a working model for how the nervous system generates goal-directed behavior.…”
Section: Discussionsupporting
confidence: 78%
“…Our design is directly inspired by the hierarchical organization of the motor system in vertebrates (16), and by its ability to pursue a hierarchy of goals in parallel, despite a complex and unpredictable environment (52). This basic design is in agreement with extensive experimental work in neuroscience (5, 6, 7, 8, 20, 21, 26, 27), and the efficacy of this design supports input control hierarchies as a working model for how the nervous system generates goal-directed behavior.…”
Section: Discussionsupporting
confidence: 78%
“…This classical approach has been substituted in some recent papers by optogenetic classification of dopamine neurons (Coddington and Dudman, 2018;Mohebi et al, 2019). We and others have observed that the waveform and firing rate of optogenetically identified dopamine neurons is consistent with classically defined criteria (Stauffer et al, 2016;Hughes et al, 2020). Here, we were not able to repeat the opto-tagging characterization because the short time-frame of the adolescent experiments (less than 3 weeks between weaning and the start of recording) does not allow for sufficient viral expression required for optogenetic tagging of dopamine neurons.…”
Section: Static and Dynamic Characteristics Of Vta And Sn Dopamine Neurons Are Similar Between Adolescents And Adultsmentioning
confidence: 87%
“…Is it the case that there are distinct populations of dopamine neurons, or timescales of activity, for signalling reward prediction errors and triggering movements, or might there instead still be a unifying framework that formally captures the relationship of dopamine activity to both? In this issue of Current Biology, Hughes et al [3] report intriguing new results which support the idea that the activity of dopamine neurons in the ventral tegmental area can be captured by a shared variable: the animal's impulse vector, or the forwards and backwards forces it exerts over time.…”
Section: ''Nothing Happens Until Something Moves''mentioning
confidence: 94%
“…In this vein, Hughes et al [3] employed 'orthogonal sensors' to enable precise measurement of the forces produced in different directions as mice received regular deliveries of rewards on a fixed time schedule. By combining this with electrophysiological recordings, some using optogenetic identification to distinguish dopamine-from nondopamine-containing neurons, they were able to identify three classes of dopamine neurons in the ventral tegmental area with firing patterns tightly correlated to force production: Fast Backward neurons, which increased their firing rates with the production of backwards force and decreased them with the production of forward force; and Fast Forward and Slow Forward neurons, which have opponent firing rates to fast backward neurons, on fast (subsecond) and slow (several second) timescales, respectively.…”
Section: ''Nothing Happens Until Something Moves''mentioning
confidence: 99%